The Changes in Pharyngeal Constrictor Muscles Related to Head and Neck Radiotherapy: A Systematic Review - Grepl, Jakub; Sirak, Igor; Vosmik, Milan; Tichy, Ales (Technology in cancer research & treatment, 2020)
It is well known that radiation damage of the pharyngeal constrictor muscles, the glottic larynx, and the supraglottic larynx may lead to dysphagia, an unwanted effect of head and neck radiotherapy. The reduction of radiotherapy-induced dysphagia might be achieved by adaptive radiotherapy. Although the number of studies concerning adaptive radiotherapy of head and neck cancer is continuously increasing, there are only a few studies concerning changes in dysphagia-related structures during radiotherapy.The goal of this review is to summarize the current knowledge about volumetric, dosimetric, and other changes of the pharyngeal constrictor muscles associated with head and neck radiotherapy. A literature search was performed in the MEDLINE database according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The conclusions of 8 studies that passed the criteria indicate a significant increase in the volume and the thickness of the pharyngeal constrictor muscles during radiotherapy. Moreover, the changes in magnetic resonance imaging signal intensity of the pharyngeal constrictor muscles correlate with the absorbed dose (typically higher than 50 Gy) and also with the grade of dysphagia. This systematic review presents 2 variables, which are suitable for estimation of radiotherapy-related pharyngeal constrictor muscles changes-magnetic resonance imaging signal intensity and the thickness. In the case of the thickness, there is no consensus in the level of the measurement-C2 vertebra, C3 vertebra, and the middle of the craniocaudal axis are used. It seems that reference to a position associated with a vertebral body could be more reproducible and beneficial for future research. Although late pharyngeal toxicity remains a challenge in head and neck cancer treatment, better knowledge of radiotherapy-related changes in the pharyngeal constrictor muscles contributes to adaptive radiotherapy development and thus improves the treatment results.
Keywords: Organs at Risk; Magnetic Resonance Imaging; Humans; nádory hlavy a krku; Radiotherapy Dosage; lidé; kritické orgány; faryngální svaly; Deglutition Disorders; Head and Neck Neoplasms; magnetická rezonanční tomografie; Pharyngeal Muscles; celková dávka radioterapie; poruchy polykání; Tomography, X-Ray Computed; počítačová rentgenová tomografie